The Extent of the Effectiveness of Consumer Protection Associations’ Role in the Iraqi Consumer Protection Law No. 1 of 2010 - Rawa Kakarash Said Mina (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
The tremendous and rapid development in consumer life and its complexity has necessitated the provision of more effective protection than before, which has made the legislations to be interested in consumer protection associations to keep pace with this development through take their ability to confront and address what harms the consumer and his rights into consideration, and they play their role in framework Legislations allowed towards it. This research is an attempt to ascertain the quantity of effectiveness of consumer protection associations’ role in the Iraqi Consumer Protection Law No. 1 of 2010 compared to the Lebanese, Yemeni, and Egyptian laws via two main topics. The first topic introduces consumer protection associations and their role in consumer protection. Moreover, the second topic deals with the role of consumer protection associations in the Iraqi Consumer Protection Law No. 1 of 2010.Finally, the research has concluded with the most important results and recommendations in a way that consumer protection associations in the previous mentioned law have a small role that lacks effectiveness.